O discurso do patrocinador: a retórica do consumo cultural das marcas - Nogueira, Jonas Santos (2019)
The research project aims to investigate the modes of functioning of the discourse and the articulated meanings for the brands – as sponsors – and for cultural productions – as sponsored – observing the logics of production of business sponsorship of culture, linked to consumption. It is based on the understanding that sponsorship has a hybrid nature, formed by an investment dimension and advertising mechanism that serves the construction of trademarks – their possible worlds. For this, the mark appropriates materially and symbolically of the cultural productions to compose its intelligible universe of signification and communicate with your audiences. We take this appropriation as a type of specific consumption of production – the cultural consumption of the – that takes place in the sponsor's speech. In order to analyze the workings of this discourse, we start from the experience of three companies sponsoring culture in Brazil – Petrobras, Natura e Itaú –, using as empirical objects the advertising films of its sponsorship programs and in-depth interviews with managers (decision makers), in order to understand the senses and the logics of production that are articulated in this process. The purpose of the study is to contribute to the expansion of studies about the interconnections between communication and consumption and the theorization of cultural sponsorship in Brazil.